CAR requires Gadd45β to promote phenobarbital-induced mouse liver tumors in early stage - Hori, Takeshi; Yokobori, Kosuke; Moore, Rick; Negishi, Masahiko; Sueyoshi, Tatsuya (Frontiers in Oncology, 2023)
Phenobarbital (PB) is an archetypal substance used as a mouse hepatocellular carcinoma (HCC) promotor in established experimental protocols. Our previous results showed CAR is the essential factor for PB induced HCC promotion. Subsequent studies suggested Gadd45β, which is induced by PB through CAR activation, is collaborating with CAR to repress TNF-α induced cell death.Here, we used Gadd45β null mice (Gadd45β KO) treated with N-diethylnitrosamine (DEN) at 5 weeks of age and kept the mice with PB supplemented drinking water from 7 to 57 weeks old.Compared with wild type mice, Gadd45β KO mice developed no HCC in the PB treated group.Increases in liver weight were more prominent in wild type mice than KO mice. Microarray analysis of mRNA derived from mouse livers found multiple genes specifically up or down regulated in wild type mice but not null mice in DEN + PB groups. Further qPCR analysis confirmed two genes, Tgfbr2 and irisin/Fndc5, were up-regulated in PB treated wild type mice but no significant increase was observed in Gadd45β KO mice. We focused on these two genes because previous reports showed that hepatic Irisin/Fndc5 expression was significantly higher in HCC patients and that irisin binds to TGF-β receptor complex that includes TGFBR2 subunit. Our results revealed irisin peptide in cell culture media increased the growth rate of mouse hepatocyte-derived AML12 cells.Microarray analysis revealed that irisin-regulated genes in AML12 cells showed a significant association with the genes in the TGF-β pathway. Expression of irisin/Fndc5 and Tgfbr2 induced growth of human HCC cell line HepG2. Thus, Gadd45β plays an indispensable role in mouse HCC development regulating the irisin/Fndc5 and Tgfbr2 genes.